2008
DOI: 10.1074/jbc.m805670200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Pharmacological Effects of Inhibitors of Signal Peptide Peptidase and γ-Secretase

Abstract: Signal peptide peptidase (SPP) and ␥-secretase are intramembrane aspartyl proteases that bear similar active site motifs but with opposite membrane topologies. Both proteases are inhibited by the same aspartyl protease transition-state analogue inhibitors, further evidence that these two enzymes have the same basic cleavage mechanism. Here we report that helical peptide inhibitors designed to mimic SPP substrates and interact with the SPP initial substrate-binding site (the "docking site") inhibit both SPP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…19,20 However, only the monomeric form of SPP was labeled with the active site-directed photoprobe III-63. 33,34 Additionally, endogenous DDM-solubilized human and drosophila SPP formed higher molecular weight complexes around 180−200 kDa. 21 We utilized a photolabeling approach to elucidate whether endogenous active SPP is a homodimer or monomer.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 However, only the monomeric form of SPP was labeled with the active site-directed photoprobe III-63. 33,34 Additionally, endogenous DDM-solubilized human and drosophila SPP formed higher molecular weight complexes around 180−200 kDa. 21 We utilized a photolabeling approach to elucidate whether endogenous active SPP is a homodimer or monomer.…”
Section: Resultsmentioning
confidence: 99%
“…2005). However, recent data have also selectively identified the NTF (Sato et al. 2008b) as well as the CTF (Sato et al.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the site was mapped at the NTF/CTF interface (Kornilova et al 2005). However, recent data have also selectively identified the NTF (Sato et al 2008b) as well as the CTF (Sato et al 2008a). In the latter, a single docking site residue has been identified in the luminal oriented side of TMD9 (Sato et al 2008a), which has been proposed to possibly function as lateral gate for substrate entry to the catalytic active site (Sato et al 2008a;Tolia et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…SPP utilizes two functional sites for the intramembrane cleavage, i.e. the initial substrate binding site and the catalytic site, which are directly targeted by the helical peptide-and the transition state analog-type inhibitors, respectively (8,22,31). A previous report indicated that both sites were present in the recombinant C-terminal fragment of dSPP (43).…”
Section: N-terminal Region Of Spp Is Responsible For Tetramericmentioning
confidence: 99%